Efektivitas Peraturan Bupati Gresik Nomor 93 Tahun 2021 Tentang Peraturan Pelaksanaan Peraturan Daerah Kabupaten Gresik Nomor 3 Tahun 2020 Tentang Penyelenggaraan Dan Retribusi Parkir - Kurniawan, Dito; Dodi Jaya Wardana (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
This research aims to find out the revenue effectiveness of implementing parking fees by the transportation agency, which is directly authorized by the Regent. Regional Original Revenue (PAD) has various sources of income funds, one of which is parking restitution revenue, especially in Gresik district, which is then used for the development of Gresik district. This study uses empirical legal research methods. The data sources that have been obtained through interviews with informants are from the Gresik Regency Transportation Service and also the Regent's Regulation Number 93 of 2021 concerning Regulations for the Implementation of Gresik Regency Regional Regulation Number 3 of 2020 concerning Implementation and Parking Retribution. The results of this study show that in 2019-2020 it can be said to be effective, but it will not be effective in 2021 with a parking fee revenue percentage of only 28.84%. Factors causing this decrease in income are parking attendants who do not tap parking daily income, as well as a lack of public awareness when paying for parking by not asking for a ticket that has been provided by the transportation agency. This shows the lack of effectiveness in managing parking fees that occur in the field.